Correlates of sleep disturbances in depressed older persons: the Netherlands study of depression in older persons (NESDO). (1st February 2018) - Peters van Neijenhof, Rian Johanna Gerdina; van Duijn, Erik; Comijs, Hannie C.; van den Berg, Julia F.; de Waal, Margot W. M.; Oude Voshaar, Richard C.; van der Mast, Roos C.
ABSTRACT: Objectives: Sleep disturbances are common among depressed older persons. To gain insight into sleep disturbances in late-life depression, their occurrence and correlates were assessed. Methods: Baseline data of 294 depressed older persons of the Netherlands Study of Depression in Older persons study were used. A diagnosis of current depression according to the diagnostic and statistical manual of mental disorders-IV (DSM-IV) was assessed with the Composite International Diagnostic Interview. Sleep disturbances were measured with the five-item Women's Health Initiative Insomnia Rating Scale, and considered present with a score of ≥10 points. Results: Sleep disturbances were present in 59.9% of the depressed older persons. Bivariate linear regression analyses showed that presence of sleep disturbances was associated with fewer years of education, use of alcohol, the number of chronic diseases, higher pain intensity scores, use of more benzodiazepines, more anxiety and severity of depressive symptoms. In multivariate analyses, severity of depression appeared to be the only independent correlate. Conclusions: Sleep disturbances are highly prevalent in patients with late-life depression and independently correlated with the severity of depression. Treatment of depression may result in improvement of sleep disturbances, although cognitive behavioral interventions that focus on both depression and sleep disturbances may also be effective.